(2x+6)(x+2)=144

Simple and best practice solution for (2x+6)(x+2)=144 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+6)(x+2)=144 equation:



(2x+6)(x+2)=144
We move all terms to the left:
(2x+6)(x+2)-(144)=0
We multiply parentheses ..
(+2x^2+4x+6x+12)-144=0
We get rid of parentheses
2x^2+4x+6x+12-144=0
We add all the numbers together, and all the variables
2x^2+10x-132=0
a = 2; b = 10; c = -132;
Δ = b2-4ac
Δ = 102-4·2·(-132)
Δ = 1156
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1156}=34$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-34}{2*2}=\frac{-44}{4} =-11 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+34}{2*2}=\frac{24}{4} =6 $

See similar equations:

| 9x−6=6x+9 | | -14d=-84 | | n2+10n+25=0 | | x^2+5x+3x+1=0 | | 3x-5(x-5)=-4+3x-11 | | 3-4(3-4x)=0 | | -8−4m=-3m | | (2y+5)(y+4)=2 | | 52.82x3-6.36x2-1101.96=0 | | 3+5x-4-7x=2x+4x+1 | | 8-3(6x+9)=4 | | 8-n+4(1+5n)=-6n-14 | | (4z/−16)=-2 | | 2w−5=5 | | 6=4+2n | | -8=2x-5x | | w-1/4=1/4 | | 4.3+x=7.6 | | -4(v-3)=-2v-4 | | 04(5x-2)=2(9x+3 | | v3+v4=56 | | 14+5=3x | | 2x+x+2x=540 | | x=1.5(-4) | | 8=4s=s+13 | | 10x-4(7x+1-(-88)+6=0 | | -5(p+53​)=-4 | | -3r+4=-20 | | 28x-(8x-7)=67 | | -3(t+5)+(4t+42)=8 | | -3(t+5)+42=8 | | 2x-6=6x-54 |

Equations solver categories